Giant Gastrointestinal Stromal Tumor with Double Bowel Obstruction Diagnostic and Therapeutic Challenges-Case Report - GNANGNON, FREDDY HOUEHANOU RODRIGUE; YACOUBOU, IMOROU SOUAIBOU; GBESSI, GASPARD DANSOU; MELI, Anicet; TAKIN, Romulus; Lawani, ismail; KPOSSOU, ABOUDOU RAÏMY; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; OLORY-TOGBE, JEAN-LÉON TOUSSAINT (My University, 2017)
Background: Gastrointestinal stromal tumors are the most common mesenchymal tumors of the digestive tract with expression of phenotype KIT/CD117 and CD34+. The stomach and small intestine are the favored sites of occurrence. The most common complication is a gastrointestinal bleeding, bowel obstruction being rare and often associated with very large tumors. Case report: We describe a 62-years-old woman presented with symptoms of abdominal pain, increased volume of the abdomen. Clinical examination revealed mild abdominal distension and a large epigastric mass. Abdominal CT scan revealed a large abdominal mass presenting mixed structure. Intraoperative findings showed a large cystic mass with solid area of 30/20 cm invading the jejunum and the transverse colon. We performed an en-block resection of the mass with a segmental resection of the transverse colon and jejunum followed by manual end-to- end anastomosis. Histo-pathological examination revealed a large gastrointestinal stromal tumor invading the jejunum and the colon. Conclusion: Jejunal and colonic gastrointestinal stromal tumors are not common and can present as bowel obstruction. The surgical management of a giant GIST can be a particularly complex challenge. It is imperative to avoid rupture of the tumor capsule as it is associated to poor outcomes. Tumor size is one of the main prognosis factors.
Keywords: Giant tumor; Colon; Jejunum; GIST; Bowel obstruction